Governance and Private Standards in Costa Rica’s Agro-Export Sector - Gómez Castillo, David (2026)
This technical note analyzes the main international standards and technical certifications adopted by the Costa Rican agro-export sector in the context of increasing private regulation in global agri-food trade. Unlike consumer-facing labels, the analysis focuses on standards that operate as business-to-business requirements and contractual conditions affecting organizational management, food safety, environmental sustainability, and social responsibility. The study systematizes quality and environmental management systems, Good Agricultural Practices certifications, internationally recognized food safety schemes, and social responsibility and ethical audit protocols. These instruments function as mechanisms for risk management, traceability, reduction of information asymmetries, and coordination within global value chains. The analysis also discusses their economic implications and the compliance costs associated with certification, particularly for small and medium-sized enterprises. This study contributes to understanding the role of private standards as instruments of governance and competitiveness in Costa Rica’s agro-export value chains